2010
DOI: 10.1007/s11160-010-9161-y
|View full text |Cite
|
Sign up to set email alerts
|

Organogenesis and histological development of the wedge sole Dicologoglossa cuneata M. larva with special reference to the digestive system

Abstract: In this work, several features during the wedge sole larval development have been described. The newly hatched larva presented an acidophilic yolk with some oil drops. The digestive tract began to differentiate at 1 DAH, with a loop being discernible. The pancreas and liver were completely formed at 2 DAH, the former showing its typical basophilic acinar structure and acidophilic zymogen granules. The first supranuclear vesicles in enterocytes were seen at 3 DAH. At 4 DAH, yolk reserves were completely exhaust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Jaroszewska et al () suggested that, for agastric fish, the appearance of the numerous mucous cells in the esophageal epithelium was considered as morphological adaptation substituting for a functional stomach. The function of pregastric digestion in esophagus had been reported by a number of researchers (Baglole et al ; Ortiz‐Delgado et al ; Gisbert et al ; Herrera et al ). Apart from the function of pregastric digestion, the secretion of mucous cells facilitated the passage of food through the esophagus (Mai et al ), and also played a role in protecting the digestive mucosa from viral and bacterial attacks (Gisbert et al ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Jaroszewska et al () suggested that, for agastric fish, the appearance of the numerous mucous cells in the esophageal epithelium was considered as morphological adaptation substituting for a functional stomach. The function of pregastric digestion in esophagus had been reported by a number of researchers (Baglole et al ; Ortiz‐Delgado et al ; Gisbert et al ; Herrera et al ). Apart from the function of pregastric digestion, the secretion of mucous cells facilitated the passage of food through the esophagus (Mai et al ), and also played a role in protecting the digestive mucosa from viral and bacterial attacks (Gisbert et al ).…”
Section: Discussionmentioning
confidence: 81%
“…Among these organs and systems, the ontogenetic development of the digestive system deserved special attention because knowledge of differentiation of the digestive tract during ontogenetic development was essential for understanding the digestive physiology of larval fish, and synchronizing the physiological stage of development with feeding practices and rearing protocols (Baglole et al 1997; Mai et al ). Up to date, researches have been conducted to determine the ontogenetic development of the digestive tract for a number of economically important fish species (Cahu and Zambonino‐Infante ; Mai et al ; Herrera et al ; Yang et al ). The majority of these studies had been involved in gastric fish, and the development of the gastric glands and the pyloric caeca was considered the last major event for larval period (Baglole et al ).…”
mentioning
confidence: 99%
“…A similar pattern has been observed in other cephalopod species, such as Sepia officinalis and Sepioteuthis lessoniana (Semmens 2002), where cephalopods reached their total development several days after hatching (Boucaud-Camou & Boucher-Rodoni 1983). This is not exclusive to cephalopods; Herrera et al (2010) proposed and defined 3 stages for the digestive development of sole Dicologoglossa cuneata larvae, according to the feeding category and the timing of ingestion, as well as digested food as: Stage 1 or endotrophic (0 to 1 DPH, larvae only fed on vitellus), Stage 2 or mixed feeding (2 to 3 DPH, exogenous and endogenous feeding) and Stage 3 or exotrophic (4 to 33 DPH, exclusively exogenous feeding with total yolk exhaustion).…”
Section: Discussionmentioning
confidence: 99%
“…In some species, like Dicologoglossa cuneata , these organs develop, while the larva feeds on the endogenous reserves, being rapidly functional after hatching (Hoehne‐Reitan and Kjørsvik ; Herrera et al . ). The presence of zymogen granules in the exocrine pancreas, observed in the studied E. anchoita stages, would support this fact.…”
Section: Discussionmentioning
confidence: 97%